The role of available phosphorous in vanadate decontamination by soil indigenous microbial consortia. (15th November 2021) - Zhang, Han; Zhang, Baogang; Gao, Yueqi; Wang, Yu; Lu, Jianping; Chen, Junlin; Chen, Dandan; Deng, Qingling
Abstract: Indigenous microbial consortia are closely associated with soil inherent components including nutrients and minerals. Although indigenous microbial consortia present great prospects for bioremediation of vanadate [V(V)] contaminated soil, influences of some key components, such as available phosphorus (AP), on V(V) biodetoxification are poorly understood. In this study, surface soils sampled from five representative vanadium smelter sites were employed as inocula without pretreatment. V(V) removal efficiency ranged from 81.7 ± 1.4% to 99.5 ± 0.2% in batch experiment, and the maximum V(V) removal rates were positively correlated with AP contents. Long-term V(V) removal was achieved under fluctuant hydrodynamic and hydrochemical conditions in column experiment. Geobacter and Bacillus, which were found in both original soils and bioreactors, catalytically reduced V(V) to insoluble tetravalent vanadium. Phosphate-solubilizing bacterium affiliated to Gemmatimonadaceae were also identified abundantly. Microbial functional characterization indicated the enrichment of phosphate ABC transporter, which could accelerate V(V) transfer into intercellular space for efficient reduction due to the structural similarity of V(V) and phosphate. This study reveals the critical role of AP in microbial V(V) decontamination and provides promising strategy for in situ bioremediation of V(V) polluted soil. Graphical abstract: Image 1 Highlights: Surface soils in vadose zone from five vanadium smelters were employed as inocula. V(V) in groundwater was efficiently removed by soil indigenous microbial consortia. Maximum V(V) removal rates were positively correlated with available phosphorous. Geobacter and Bacillus catalytically reduced V(V) to insoluble V(IV). Phosphate ABC transporter was enriched for V(V) transfer as structural similarity.